1998
DOI: 10.1016/s0092-8674(00)81134-4
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of Hammerhead Ribozyme Self-Cleavage

Abstract: We have captured an 8.7 A conformational change that takes place in the cleavage site of the hammerhead ribozyme during self-cleavage, using X-ray crystallography combined with physical and chemical trapping techniques. This rearrangement brings the hammerhead ribozyme from the ground state into a conformation that is poised to form the transition state geometry required for hammerhead RNA self-cleavage. Use of a 5'-C-methylated ribose adjacent to the cleavage site permits this ordinarily transient conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
223
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(240 citation statements)
references
References 44 publications
14
223
0
3
Order By: Relevance
“…The second, globally minor, structural adjustment coincides with activation of the ribozyme at high Mg 2+ concentrations (90 mM for HHL and 10 mM for HHR). Our data are therefore largely consistent with the notions, suggested first by X-ray crystallography, that the functionally relevant conformation has stems I and II at an acute angle and that only a relatively small conformational change is required to reach the catalytic transition state (5,17,22,43). Additionally, we note that throughout the entire Mg 2+ range, HHR has a more flexible stem I-stem II distance than HHL (Figure 6), an observation that may relate to its higher catalytic activity, consistent with the activation entropy increase previously reported (25).…”
Section: Discussionsupporting
confidence: 91%
“…The second, globally minor, structural adjustment coincides with activation of the ribozyme at high Mg 2+ concentrations (90 mM for HHL and 10 mM for HHR). Our data are therefore largely consistent with the notions, suggested first by X-ray crystallography, that the functionally relevant conformation has stems I and II at an acute angle and that only a relatively small conformational change is required to reach the catalytic transition state (5,17,22,43). Additionally, we note that throughout the entire Mg 2+ range, HHR has a more flexible stem I-stem II distance than HHL (Figure 6), an observation that may relate to its higher catalytic activity, consistent with the activation entropy increase previously reported (25).…”
Section: Discussionsupporting
confidence: 91%
“…5 were achieved using a near-axial ZFS tensor (E/D = 0.1), a finding supported by the axial geometry observed in the crystal structure of the Mn(II)EDTA complex [112]. As this species serves to calibrate our water-counting measurements via ESEEM spectroscopy, the MF EPR spectroscopic characterization of Mn(II)EDTA presented here is essential to extending these types of studies to higher frequencies [98,114].In conclusion, the MF EPR approach is not only useful in determining spin Hamiltonian parameters for paramagnetic systems (Eq. (2)) but may also provide clues as the degree of homogeneity associated with the binding site of the metal cofactor.…”
mentioning
confidence: 60%
“…Biochemical and EPR spectroscopic studies carried out by DeRose and coworkers [92,94] found that only one of these sites tightly binds its respective metal ion (k d ≤ 10 µM), and that this site must be populated for "catalytic" activity. However, all available spectroscopic evidence indirectly suggested that the high-affinity binding site exists between the N7 of a guanine residue (G10.1) and the phosphate oxygen of an adjacent adenine (A9), about 2.0 nm from the site of RNA cleavage [35,92,[95][96][97][98].Only recently has this tentative assignment been confirmed through ESEEM spectroscopic measurements of site-specific isotope labeling of the G10.1 nitrogens [99]. Herein, we report results from EPR spectroscopic experiments at multiple frequencies to study a set of simple nucleotide and RNA Mn(II) complexes.…”
mentioning
confidence: 99%
“…The final ribose MePA 2− residue was fit within the RNA sequence UCA taken from the near in-line geometry in the x-ray crystal structure of a hammerhead ribozyme "late-intermediate". 74 ABNR minimization was performed for this sequence with the U and A residues fixed and where necessary, small adjustments to the internal parameters were made to improve fitting. Because the pentacoordinated geometry of the phosphorane is quite rigid, the dihedrals had negligible effect, and hence were set to zero.…”
Section: Phosphate Transition State Analogmentioning
confidence: 99%